Fa’āliyatu Tanfīdzi Istirātījiah (Silent Demonstration) Bi Wasīlati (Charades App) Fī Māddati al-Lughah al-‘Arabiyah Li Raf’i Nasyāthi Ta’allumi ath-Thullāb wa Natāijihim - Rahmanudin, Ii (Journal of Language Intelligence and Culture, 2022)
Learning Arabic requires a good learning strategy. Hence, it is necessary to make changes and improvements in the learning process. One of the strategies that can improve students’ learning outcomes is the implementation of the Silent Demonstration Strategy with the Charades App. This research used Classroom Action Research design. This research was conducted at SMA Islam Al-Azhar 24. The research process involved two teaching and learning cycles, which cover the aspect of planning, implementation, observation, and reflection. The data was collected through test, observation, and documentation. The results of this study are as follows. 1) The implementation of the Silent Demonstration Strategy with the Charades App can increase student’s learning activity in which  in the first cycle of learning activity, 75% of students optimally engaged within the learning process and it increased up to 100% in the cycle 2. 2) The application of the Silent Demonstration Strategy with the Charades App can improve student learning outcomes where 40% of studentgot average score of 5.42 and the second cycle, 90% of students got an average score of 6.97. Teachers are expected to be able to apply learning strategies that are in accordance with the Arabic learning process.